2015
DOI: 10.1155/2015/480764
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking of Potential Inhibitors for Influenza H7N9

Abstract: As a new strain of virus emerged in 2013, avian influenza A (H7N9) virus is a threat to the public health, due to its high lethality and pathogenicity. Furthermore, H7N9 has already generated various mutations such as neuraminidase R294K mutation which could make the anti-influenza oseltamivir less effective or ineffective. In this regard, it is urgent to develop new effective anti-H7N9 drug. In this study, we used the general H7N9 neuraminidase and oseltamivir-resistant influenza virus neuraminidase as the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Moreover, intravenous injection of CHA could be an optional administration route. Taken together, the antiviral effects of CHA against influenza virus were demonstrated in this study, which agrees with findings of previous studies1723242526. Importantly, CHA could be the potential antiviral material basis of Lonicera japonica Thunb34, Reduning35 and Shuanghuanglian injection36.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, intravenous injection of CHA could be an optional administration route. Taken together, the antiviral effects of CHA against influenza virus were demonstrated in this study, which agrees with findings of previous studies1723242526. Importantly, CHA could be the potential antiviral material basis of Lonicera japonica Thunb34, Reduning35 and Shuanghuanglian injection36.…”
Section: Discussionsupporting
confidence: 92%
“…CHA was reported to reduced serum hepatitis B virus level in vivo 20. Results from molecular docking experiments indicated that CHA could be a potential NAI of influenza virus H1N123, H5N124 and H7N925. It was reported that CHA could recover cell viability and increase survival rate in H1N1-infected mice23.…”
mentioning
confidence: 99%
“…The experiments with the four neuraminidases were carried out in presence of the reference drug zanamivir. The catalytic residues within the active sites were identified as R118, R292 and R371 at subsite S1 and D151 at subsite S2, R152 at subsite S3, and E276 [ 9 , 17 , 36 , 37 ]. They are all interacting with zanamivir whose binding mode allows the drug to tightly attach to the viral enzyme and strongly inhibit the enzymatic activity, since the aforementioned residues are necessary for natural substrate recognition ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…is is supported by a number of studies which predicted the high binding ability (indicated as highly negative docking scores) of small molecules to protein of interest can be correlated to their protein inhibitory property, which resulted in downregulation of protein as observed in in vitro studies and comparable with known inhibitor for that particular protein [41][42][43]. Binding of ligand (EGCG) to a protein (FtH) may result in inhibition of the protein expression, which simultaneously will downregulate the expression of the protein.…”
Section: Ferritin Was Identified As a Probable Target For Egcgmentioning
confidence: 85%